2019
DOI: 10.1016/j.genhosppsych.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Bringing close others to the emergency department for an acute coronary event is associated with increased patient perception of threat

Abstract: Objective: Relationship quality is one of the most consistent psychosocial predictors of physical and mental health. Yet, little research examines relationship types or support within the immediate context of acute health events. We tested the unexplored role that close others play in patients’ experience of threat during evaluation for acute coronary syndrome (ACS) in the Emergency Department (ED), as well as the indirect effect of close others on ACS-induced posttraumatic stress disorder (PTSD). Method: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…Emerging research has begun to illuminate the potential for negative psychological effects in patients who have a close other, such as a spouse or romantic partner, present during early emergency care. For example, one study conducted at an urban medical center in the United States found that patients in the ED with close others reported feeling more threatened, helpless, and vulnerable when asked to recall their ED experience only a few days later (Cornelius et al, 2019a). There was no impact of the presence of a partner on patient anxiety in the current study, however.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Emerging research has begun to illuminate the potential for negative psychological effects in patients who have a close other, such as a spouse or romantic partner, present during early emergency care. For example, one study conducted at an urban medical center in the United States found that patients in the ED with close others reported feeling more threatened, helpless, and vulnerable when asked to recall their ED experience only a few days later (Cornelius et al, 2019a). There was no impact of the presence of a partner on patient anxiety in the current study, however.…”
Section: Discussioncontrasting
confidence: 71%
“…We hypothesized the link between partner presence and partner PSS because presence can be seen as similar to trauma exposure (Vilchinsky, 2017;Vilchinsky and Dekel, 2018). However, since in a prior study, we did not find evidence for a direct effect of close others on distress distal to an acute coronary syndrome (ACS) in patients (Cornelius et al, 2019a), we refrained from hypothesizing the same link for patients. We anticipated that partners who were not at all exposed to the event would be the least distressed.…”
Section: Early Exposure To Cardiac Treatment and Distress Among Patiementioning
confidence: 95%
See 2 more Smart Citations
“…An acutely life‐threatening medical event may represent a highly sensitive window in which novel health behaviors are initiated and the transition to established patterns of chronic illness management begins (or changes to prior management behaviors are necessitated). Early distress can also develop within each member of the dyad, which may undermine the benefits of relationships for patient health and well‐being (Cornelius, Derby, et al., 2020; Cornelius, et al., 2019). Distress also undermines the initiation of health behaviors for secondary prevention (e.g., physical activity, medication adherence), which has long‐term implications for physical health (Cornelius, Agarwal et al., 2018; Edmondson, Horowitz et al., 2013; Edmondson et al., 2012; Edmondson, Richardson et al., 2013; Fait et al., 2017; Kronish et al., 2014, 2006; Vilchinsky, 2017).…”
mentioning
confidence: 99%